ANALISIS PRODUKSI KARET RAKYAT DI DESA PONTANGOA KECAMATAN LEMBO RAYA KABUPATEN MOROWALI UTARA - Pujianti, Ratna; Antara, Made (AGROTEKBIS, 2016)
This research aimed to identify factors influencing rubber production of people plantation in of Pontangoa village LemboRaya sub-districton North Morowali Regency. This research was carried out in November â December 2015. Respondents were determined using a Random Sampling Technique. The number of the respondents was 31 families selected from a population of 407 farmers. Data was analyzed using the Cobb-Douglas analysis. The results showed that all the variables are simultaneously highly significant affecting the production of the rubber, where F-counted is 545.377 > F-table (3.85) at Î± of 5%, thus H0 is rejected and H1is accepted.Such factors as land area, plant number, and labor have partially significant effect on the rubber production as shown by t-counted of land area (4.759) is >t-table (2.478), t-counted of plant number (6.236)>t-table (2.478), and t-counted of labor (-2.567)>t-table (2.478) suggesting that the H1 for these factors is accepted.Â By contrast, fertilizer (SP36) and farmer experience have no significant effect as indicated by t-counted of the SP-36 (0.238)<t-table (2.499) and t-counted the farming experience (1.8538)<t-table (2.478) leading to that the H0 of these factors is acceptedÂ Key Words: People plantation and Production of rubber.